2022
DOI: 10.3390/cancers14030795
|View full text |Cite
|
Sign up to set email alerts
|

A Double-Negative Feedback Interaction between miR-21 and PPAR-α in Clear Renal Cell Carcinoma

Abstract: Clear cell renal cell carcinoma (ccRCC) is the main histotype of kidney cancer, which is typically highly resistant to conventional therapies and known for abnormal lipid accumulation. In this context, we focused our attention on miR-21, an oncogenic miRNA overexpressed in ccRCC, and peroxysome proliferator-activated receptor-α (PPAR- α), one master regulator of lipid metabolism targeted by miR-21. First, in a cohort of 52 primary ccRCC samples, using RT-qPCR and immunohistochemistry, we showed that miR-21 ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…In addition, the content of TG in cells decreased with the increase in arsenic exposure dose. In the study of lipid metabolism in mice exposed to low-dose arsenic, it was found that chronic arsenic exposure could induce the decrease in SREBP-1c expression in the liver, which decreased TG synthesis in hepatocytes [36], and it was consistent with the results of this study. Although the expression levels of SREBP-1c and its downstream gene FASN were decreased, hepatocyte steatosis still occurred in animal experiments.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, the content of TG in cells decreased with the increase in arsenic exposure dose. In the study of lipid metabolism in mice exposed to low-dose arsenic, it was found that chronic arsenic exposure could induce the decrease in SREBP-1c expression in the liver, which decreased TG synthesis in hepatocytes [36], and it was consistent with the results of this study. Although the expression levels of SREBP-1c and its downstream gene FASN were decreased, hepatocyte steatosis still occurred in animal experiments.…”
Section: Discussionsupporting
confidence: 90%
“…In this context, miR-21 has been shown to be involved in the resistance to conventional chemotherapies (paclitaxel, 5-Fluorouracil, topotecan and platinum-based therapy) and targeted therapies such as dovitinib and sorafenib by controlling the expression of genes associated with multi-drug resistance (MDR) and the apoptotic pathway (PTEN, PDCD4) [ 85 , 105 , 106 ]. Similar to renal fibrosis, miR-21 seems to also be involved in the metabolic shift characterizing renal cancer by targeting PPAR-α, a master regulator of lipid metabolism [ 107 ]. miR-21 silencing using antisense oligonucleotide or miR-21 sponge strategies decreases the proliferation, invasion and migration of cRCC cells and also increases the expression of pro-apoptotic markers.…”
Section: Mir-21 In Kidney Injuries and Diseasesmentioning
confidence: 99%
“…The PFAS-induced decreased expression on RAG1 and RAG2 in Namalwa cells and decreased activity of IL-2 reporter activity in Jurkat cells described here are potentially also mediated by PPARs. Upon activation, PPARs are reported to negatively interfere with nuclear factor κB (NF-κB) and (activator protein-1) AP-1 signaling pathways ( Chinettl et al, 2000 ; Harmon et al, 2011 ; Goujon et al, 2022 ) and in addition, activated PPAR-γ is reported to physically associate with nuclear factor of activated T-cells (NFAT). Upon activation of the T-cell receptor (TCR), NF-kB, AP-1, and NFAT are stimulated and bind to the canonical response element in the promoter of IL-2, leading to transcriptional regulation of IL-2 gene expression.…”
Section: Discussionmentioning
confidence: 99%